PENGARUH KUALITAS PELAYANAN AKADEMIK TERHADAP TINGKAT KEPUASAN MAHASISWA (Studi Kasus di Fakultas Teknik Prodi Teknik Industri Unisbank Semarang) - Flady Dian Pratama; Eddi Indro Asmoro (Jurnal Ilmiah Dinamika Teknik, 2020)
This research aims to measure the quality of academic service to the level of student satisfaction. Students ' complaints are based on the brain-strorming in small discussions of each generation. This research was conducted on the Faculty of Engineering Progam Industrial Engineering Study of Stikubank University of Semarang. This Research uses quantitative approaches. The population in this study is a student of the Faculty of Engineering Progam Industrial Engineering Study of Stikubank Semarang University. In this study because the population was relatively limited, the entire population in this study was made into samples (census samples), so the samples in this study amounted to 69 people. It is based on the theory expressed by (Arikunto, 1993), "if the subject of research is less than 100 people then it is better taken overall. Data collection techniques using questionnaires have tested their validity and reliability. The data analysis technique used to answer the hypothesis of this research is with the help of simple linear regression. The results showed that 40 valid statements and 6 sub-variables of reliable service quality. The level of influence on the student satisfaction level of each sub variable from the highest on the system Information sub variables with a constant value of 1,138, the second on the assurance sub-variable with a constant value of 1,111, the third on the Sub Tangibles variable with a constant value of 1,075, the fourth one in the empathy sub-variable with a constant value of-1,027, the fifth one on the responsiveness sub variable with a constant value of-1,067, and the lowest one on the reliability sub-variable with a constant value- 1,195. Keywords: Quality of academic service, student satisfaction, 6 Sub variables